Tendências e perspectivas da permanência estudantil na UFMT : entre a afirmação de direitos e a bolsificação de necessidades - Mota, Tatiane Eloize Furyama (2018)
This study presents an analysis of the conditions of stay of students assisted by the National Program of Student Assistance (PNAES) within the scope of the UFMT, Cuiabá campus. With the purpose of deepening the discussion about the importance of the student assistance policy for the permanence in the public university, we propose in this work to discuss how the assistance to the student in the UFMT has been structured. The interest in this study was determined by the concerns resulting from professional experience, experienced in the Coordination of Attendance to Students (CAE) in the IFMT in the period 2014-2017, and in the Supervision of Student Assistance (SAE) in the UFMT started in May 2017. For this, we used a quanti-qualitative approach and the adopted procedures were: bibliographic review, documentary analysis and the focus group technique. The analysis of the data was supported by a theoretical study about educational policies in the context of higher education, particularly in universities, followed by the debate on student assistance policy and the conditions of stay in the UFMT. In the first moment, we present a theoretical debate about educational policies focused on Brazilian higher education, especially from the democratization and expansion of higher education in the 1990s. Next, we discuss the political, economic and social context that fostered PNAES regulations, we delimit the space of student assistance policy in the context of the UFMT. Finally, we present the results of the research, hoping to collaborate with the process of reflection and debate about student stay in the university. It seeks to reveal to what extent the actions coming from the student assistance policy, from the PNAES, were decisive for the continuation of the course at the UFMT. We find that student permanence involves a set of material and symbolic factors that influence academic (in) success, therefore, to remain in the institution is beyond the monetary pass-through granted through scholarships and scholarships.